Effects of Tannin Extract from Gongronema latifolium Leaves on Lipoxygenase Cucumeropsis manii Seeds - Sabinus O. O. Eze; Bennett C. Nwanguma (Journal of Chemistry)
Lipoxygenase (EC 1.13.11.12) was partially purified from germinated seeds of Cucumeropsis manii to a purification fold of 47.14, enzyme activity recovery of 72.18%, and specific activity of 326.25 units/mg protein, using a three-step process of centrifugation, ammonium sulphate precipitation and gel filtration. Kinetic properties show maximum activity at pH 6.0 and at optimum temperature of 40°C. Inhibitory effects of the extract from Gongronema latifolium and two other known antioxidants: ascorbic acid and propyl gallate on lipoxygenase from Cucumeropsis manii were studied. Result shows presence of inhibition with IC50 of 4.2×10−3 ± 0.09×10−3 g/L, 4.3×10−2 ± 0.11×10−2 g/L and 7.9×10−2 ± 0.11×10−2 g/L for the extract from ascorbic acid and propyl gallate, respectively. The extract when compared to the other antioxidants exhibits a competitive mechanism of inhibition. This tannin extract could be included during food processing as preservative against food deterioration that might be caused by oxidative enzymes such as lipoxygenase.